The Effect Of Female Labor Participation On Economic Growth In Papua 2005-2019 - Cholily, Vebrina Hania (Institut Manajemen Wiyata Indonesia, 2023)
Papua Province with 23 regencies and 1 city showcases diverse sectors. Jayapura excels in agriculture, plantations, services, crude oil, and palm oil, while Timika stands out for mining. The province's economic growth relies on an increasing Gross Domestic Products. In 2020, the GDP was IDR 198.93 trillion and IDR 137.68 trillion. Notably, Papua experienced a 24.68% growth in Q2 2018, mainly due to the mining sector's contribution of 56.03%. Women in Papua play dual roles in households and the economy, yet face challenges like marginalization, subordination, double burden, stereotypes, and violence. Although Papua's Human Development Index rose to 61.39 in 2022, its health index remains low. Delivery coverage in 2013 was only 33.31%, and maternal mortality rates are high. Poor health adversely affects economic growth, reducing productivity, increasing healthcare costs, and limiting livelihood opportunities. Furthermore, low health levels hinder Papua's HDI achievement. This study explains the impact of female labor force participation on Papua's economic growth. The research focuses on the GDP by Field of Activity as the dependent variable and female labor participation as the independent variable. A sample of 15 data points will undergo multiple linear regression analysis and classical assumption tests using software EVIEWS 10. The results of this research indicate that female labor participation does not have a significant effect on Papua's economic growth.